Estimation of electron temperature for SiO2 plasma induced by laser - Abdulameer, Mohammed R. (Iraqi Journal of Physics, 2019)
In this work; Silicon dioxide (SiO2) were fabricated by pulsed laser ablation (PLA). The electron temperature was calculated by reading the data of I-V curve of Langmuir probe which was employed as a diagnostic technique for measuring plasma properties. Pulsed Nd:YA Glaser was used for measuring the electron temperature of SiO2 plasma plume under vacuum environment with varying both pressure and axial distance from the target surface. The electron temperature has been measured experimentally and the effects of each of pressure and Langmuir probe distance from the target were studied. An inverse relationship between electron temperature and both pressure and axial distance was observed.